Peranan Komunikasi Antarpribadi Guru Bimbingan Konseling (BK) Dalam Menangani Kenakalan Siswa (Studi Kasus di SMP Negeri 1 Panongan Kabupaten Tangerang) - Sukowati, Nuni Fajar; Wati, Lina; Hardiyanti, Rini (Peneliti.net, 2024)
This study aims to determine the role of interpersonal communication and the obstacles experienced by guidance counseling (BK) teachers in dealing with student delinquency at Panongan 1 Public Middle School. The type of research used is qualitative research with a qualitative descriptive approach. The informants of this study were counseling teachers and students who violated school discipline. Data collection techniques by way of observation, interviews and documentation. The data analysis technique uses the Miles and Huberman interactive analysis model. The research results show that the role of personal communication between counseling guidance teachers in dealing with student delinquency at SMP Negeri 1 Panongan is to play a role in relationship formation, providing emotional support, information exchange and behavior change . Interpersonal communication used by BK teachers in dealing with student delinquency at SMP Negeri 1 Panongan by conducting individual counseling. Based on social exchange theory, the formation of relationships between BK teachers and delinquent students is reviewed through four points, namely cost, reward, comparison, and yield or profit. The factors hindering personal communication between BK teachers in dealing with student delinquency at SMP Negeri 1 Panongan are internal and external factors. The internal factors of his obstacles face the characteristics of students who are afraid, ashamed, and not open about his problems with BK teachers. The external factor is that the unfavorable friendship environment of students will affect students to return to the unkind behavior that has been done before.